2020
DOI: 10.1177/1357633x20917497
|View full text |Cite
|
Sign up to set email alerts
|

Combined in-person and tele-delivered mobile school clinic: A novel approach for improving access to healthcare during school hours

Abstract: Aims We report a novel pilot project that allows access to healthcare for children and staff at school via a mobile clinic or telemedicine portal connected to the mobile clinic. The objectives of this pilot project were (a) to perform physicals for children not attached to a primary care physician; (b) to provide medical consultations and treatment for acute illnesses of students and staff, and (c) to lower absenteeism rates among students and staff. Methods In 2013, Ronald McDonald House Charities, a non-prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Bringing a mobile ‘clinic’ equipped with VC to the patients’ home would allow them to overcome certain technology-related barriers and ensure a controlled testing environment by allowing the patient to stay comfortably at home. One study in the US reported on a similar pilot project providing access to healthcare services to children through a telemedical service connected to a mobile clinic [ 21 ]. MU have served to extend access to early cancer screening in numerous countries [ 20 ] with encouraging outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Bringing a mobile ‘clinic’ equipped with VC to the patients’ home would allow them to overcome certain technology-related barriers and ensure a controlled testing environment by allowing the patient to stay comfortably at home. One study in the US reported on a similar pilot project providing access to healthcare services to children through a telemedical service connected to a mobile clinic [ 21 ]. MU have served to extend access to early cancer screening in numerous countries [ 20 ] with encouraging outcomes.…”
Section: Introductionmentioning
confidence: 99%